Edukasi dan Pendampingan UMKM Melalui Kube Mega Buana Terhadap Penundaan Kewajiban Sertifikasi Halal: Strategi Menuju Wajib Halal Oktober 2026 - Roihan, Muhammad; Ridhwan, Ridhwan; Enggrani Fitri, Lucky; Rafiqi, Rafiqi; Pratiwi, Heni; Dean Amri, Ary; Arfah, Arfah; Afriyanti, Suviya (PT. Alahyan Publisher Sukabumi, 2025)
The halal certification obligation for Micro, Small, and Medium Enterprises (MSMEs) products that has been set by the government through the Halal Product Assurance Agency (BPJPH) originally took effect in October 2024, now it has been extended until October 2026. However, most MSME actors, including KUBE Mega Buana in Tangkit Baru Village, Muaro Jambi Regency, are not ready to fulfill these obligations due to a lack of understanding of the certification process, limited information, and cost constraints. This service program aims to provide education and assistance to KUBE Mega Buana members to understand the importance of halal certification, know the mechanism and stages of submission, and be able to prepare the required documents independently. The approach is carried out through halal literacy training, registration simulations through the BPJPH siHalal system, and the preparation of a simple halal product management system. The results of the activity showed an increase in the understanding of KUBE Mega Buana members about halal certification obligations, the ability to identify products that must be certified, and administrative readiness in the process of applying for halal certification. This program contributes to increasing halal awareness, strengthening the competitiveness of Tangkit's typical pineapple processed products, and the readiness of MSMEs to face the implementation of mandatory halal in 2026.